Fishes from the Miocene lacustrine sequence of Bełchatów (Poland). (13th September 2020) - Kovalchuk, Oleksandr; Nadachowski, Adam; Świdnicka, Ewa; Stefaniak, Krzysztof
ABSTRACT: The paper deals with results of the study of freshwater fish remains obtained from the Miocene deposits of Bełchatów open-cast brown coal mine in 1984 and 1986. These fossils are represented mainly by numerous disarticulated bones which are assumed as belonging to cyprinid ( Tinca sp.) and esocids ( Esox sibiricus, Esox sp.), as well as to indeterminate bony fishes (Teleostei indet.). The find of the Siberian pike described herein is the oldest occurrence of this species in Europe, and allows extending its previously known range to the west. Some aspects of the palaeogeography and palaeoecology of the late early Miocene fish assemblage of Bełchatów with reference to the distribution of E. sibiricus are discussed.